Evaluation of the implant disease risk assessment (IDRA) tool: A retrospective study in patients with treated periodontitis and implant‐supported fixed dental prostheses (FDPs). Issue 11 (23rd August 2021) - De Ry, Siro P.; Roccuzzo, Andrea; Lang, Niklaus P.; Heitz‐Mayfield, Lisa J.; Ramseier, Christoph A.; Sculean, Anton; Salvi, Giovanni E.
Abstract: Aim: To evaluate the Implant Disease Risk Assessment (IDRA) tool for the prediction of peri‐implantitis in treated periodontitis patients with implant‐supported fixed dental prostheses (FDPs) after at least 5 years of function. Material and methods: From the patient pool of implant patients enrolled in a regular supportive periodontal therapy programme (SPT) for at least 5 years, 239 patients were screened. Eighty patients met the inclusion criteria and underwent evaluation through the criteria of the IDRA tool. Areas under the curve (AUCs) for receiver operating characteristic (ROC) curves including 95% confidence intervals were estimated. Results: Seventy‐nine patients (43 males and 36 females, 8 smokers), aged on average 59.0 years (range: 40–79 years) at baseline (i.e. FDP delivery) were analysed. The calculated IDRA‐risk was in 34 patients (42.5%) a moderate risk, while 45 patients (56.3%) were considered at high IDRA‐risk. One patient categorized at low IDRA‐risk was excluded from the analysis. The AUC was 0.613 (95% CI: 0.464–0.762) if the IDRA‐risk was associated with prevalence of peri‐implantitis at the most recent follow‐up. Peri‐implantitis was diagnosed in 4 patients (12%) at moderate and in 12 patients (27%) at high IDRA‐risk, respectively. The calculated odds ratio for developing peri‐implantitis in patients with high IDRA‐risk compared with patients with moderate IDRA‐risk was 2.727 with no statistically significant difference between the two groups (95% CI: 0.793–9.376). Conclusion: Within the limitations of the present retrospective study, the IDRA algorithm might represent a promising tool to assess patients at moderate or high risk of developing peri‐implantitis.